Engineering Drawing and Computer Graphics (First Angle Projection) - Gunasekaran (N); Kannan (T); Rajendran (P) ("KCT,Coimbatore", 2002)
Engineering Drawing ; Computer Graphics
Keywords: Engineering Drawing ; Computer Graphics